PENERAPAN STRATEGI DOMINO GAME DISERTAI HANDOUT PADA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS VIII SMPN 27 PADANG TAHUN PELAJARAN 2012/2013 - Sholehat, Safitri; Zuzano, Fazri; Edriati, Sofia (Pendidikan Matematika, 2013)
The background of this research about students understanding of mathematis concept is still low. The purpose of this research to know what students understanding of mathematis concept with applying Domino Game strategi with handout is more good than students understanding of mathematis concept by using convensional learning at SMPN 27 Padang. This research is experiment research with random design toward subject. The population in this research is all of student at class of VIII SMPN 27 Padang of year 2012/2013 consist of seven class of VIII.1 is best class. Technique of sampling is done by random sampling, furthermore it is chosen VIII.2 class as experiment class and VIII.4 class as control class. Instrument of this research is final test that is formed valid and reliable test in 95 %. Based hyphotesis test that use by uji t one step, in briefly students understanding of mathematis concept applay Domino Game strategi with handout which is more good than students understanding of mathematis concept with convensional learning. Be hope for the teacher can try to teach by using Domino GameÂ  strategi with handout.